We are free : you & me - Kaepernick, Colin, 1987-; Diab, Nessa; Jose, Gladys (New York, NY : Scholastic Inc., Kaepernick Publishing, 2024)
Every child has the right to be free, the right to reach, the right to dream. This lyrical affirmation of what freedom truly means celebrates the principles of Colin and Nessa's Know Your Rights Camp--an international movement that has inspired thousands of young people to rejoice in their inherent goodness.
School Library Journal, September 2024
K-3
Keywords: Liberty -- Juvenile fiction; Human rights -- Juvenile fiction; Conduct of life -- Juvenile fiction; Liberty -- Fiction; Human rights -- Fiction; Conduct of life -- Fiction; Self-esteem -- Juvenile fiction; Social justice -- Juvenile fiction